Chronic Q fever-related complications and mortality: data from a nationwide cohort. (November 2019) - van Roeden, S.E.; Wever, P.C.; Kampschreur, L.M.; Gruteke, P.; van der Hoek, W.; Hoepelman, A.I.M.; Bleeker-Rovers, C.P.; Oosterheert, J.J.
Abstract: Objectives: Chronic infection with Coxiella burnetii (chronic Q fever) can cause life-threatening conditions such as endocarditis, infected vascular prostheses, and infected arterial aneurysms. We aimed to assess prognosis of chronic Q fever patients in terms of complications and mortality. Methods: A large cohort of chronic Q fever patients was assessed to describe complications, overall mortality and chronic Q fever-related mortality. Chronic Q fever-related mortality was expressed as a case fatality rate (number of chronic Q fever-related deaths/number of chronic Q fever patients). Results: Complications occurred in 166 of 439 (38%) chronic Q fever patients: in 61% of proven (153/249), 15% of probable (11/74), and 2% of possible chronic Q fever patients (2/116). Most frequently observed complications were acute aneurysms (14%), heart failure (13%), and non-cardiac abscesses (10%). Overall mortality was 38% (94/249) for proven chronic Q fever patients (median follow-up 3.6 years) and 22% (16/74) for probable chronic Q fever patients (median follow-up 4.7 years). The case fatality rate was 25% for proven (63/249) chronic Q fever patients and 4% for probable (3/74) chronic Q fever patients. Overall survival was significantly lower in patients with complications, compared to those without complications (p <0.001). Conclusions: In chronic Q fever patients, complications occur frequently and contribute to the mortality rate. Patients with proven chronic Q fever have the highest risk of complications and chronic Q fever-related mortality. Prognosis for patients with possible chronic Q fever is favourable in terms of complications and mortality.